1988
DOI: 10.1007/bf00170774
|View full text |Cite
|
Sign up to set email alerts
|

Use of human neuroblastoma continuous cell lines for in vitro drug sensitivity screening

Abstract: We have used three continuous human neuroblastoma cell lines to establish patterns of in vitro drug sensitivities, as judged by clonogenic assay. We evaluated 12 'standard' antitumor drugs already in clinical usage, and tested four newer analogues, one of cisplatin and three of doxorubicin, and the investigational agent desferrioxamine. A certain heterogeneity of drug sensitivities was noted amongst these three cell lines, but a few general conclusions can be drawn. Responses of all lines tested were similar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Carboplatin is a potent anticancer agent. It has been demonstrated that brain tumor cells are chemosensitive to carboplatin in in vitro (Dodion et al 1988;Hill et al 1988) and in vivo (Matsukado et al 1996;Olivi et al 1996). In phase 1-11 studies, it has been effective against brain tumors (Gaynon et al 1990).…”
mentioning
confidence: 99%
“…Carboplatin is a potent anticancer agent. It has been demonstrated that brain tumor cells are chemosensitive to carboplatin in in vitro (Dodion et al 1988;Hill et al 1988) and in vivo (Matsukado et al 1996;Olivi et al 1996). In phase 1-11 studies, it has been effective against brain tumors (Gaynon et al 1990).…”
mentioning
confidence: 99%